Línea base de información geográfica para el "sistema para la gestión y manejo de incidentes por incendios forestales", Región Chorotega, Costa Rica - Molina-Quesada, Sara Elena (Instituto Tecnológico de Costa Rica, 2017)
Costa Rica is characterized by a great diversity of ecosystems, including the Dry Forest region in the northwest of the country. Due to the topographic, climatic and vegetation types, 76.88 % of the total area affected by forest fires is recorded in this zone, from 1998 to 2017. To manage the forest fire incidents in the best way, the National System of Conservation Areas (SINAC) going to make available to the staff one software with real and updated geographical information for the Guanacaste, Tempisque and Arenal - Tempisque Conservation Areas. The objective of this work was to generate the baseline of geographical information for the "System for Management of Incidents by Forest Fires". The required geographical information was identified in conjunction with the Forest Fire Technical Committee (COTENA) and the National Commission about Forest Fires (CONIFOR). In addition, a geographical information collect procedure was created to provide SINAC staff with a methodology for field use to generate data in a standardized manner at the national level. The geographic information repository was created in an orderly and standardized manner. It contains 50 layers created from the information collected by SINAC officials, six from other institutions and 33 linked from the geoportal of the National Spatial Data Infrastructure of Costa Rica (SNIT). Each layer of geographical information was given a style and saved in the Base Line Data Dictionary.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Incendios forestales; repositorios de datos; Diccionarios; Cobertura forestal; Bosques; Software